Estado e mundo do trabalho: uma análise sobre o papel do Estado e suas intervenções no mercado de trabalho - Mathis, Mariza Felipe (2020)
The modifications on the States interventions is an important theme on pollical and economical debate, given it great relevance and economical and social consequences. In the labor market, the State intervention can occur in different ways and with different results. Therefore, the investigation of this interventions and its consequences is necessary to discuss the workers’ rights and the ideological bias of the State. The main objective of this dissertations was to analyze the nature of the State and its actions on labor market. For that, we explored a variety of State’s theories, as the classic, liberal, marxists and neoliberal. After that, we carried out a historical approach of ones of the most important State intervention on labor market in central capitalist countries. The main result of this work was to related that the capitalism State, that is, a State ruled by the bourgeois class, dictates the norms and regulations of the labor world according to their needs and, thus, keeps the working class submissive to the interest of the bourgeois class